The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.22598/mt/2019.31.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Corporate Reputation and Pride as Drivers of Frontline Employees’ Reputation Impact Awareness: Mediating Role of Job Satisfaction

Abstract: Purpose-Service employees play a crucial role in creating and sustaining the reputation of service fi rms. Their attitudes and commitment to the fi rm are refl ected in customers' perceptions of quality and loyalty, which ultimately improve corporate performance. The aim of this study is to better understand what contributes to raising frontline employees' awareness of their role in building and sustaining the corporate reputation of service fi rms. Design/methodology/approach-We adapt Helm's (2011) conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Attitudinal pride (in contrast to the individuality of emotional pride) is collective and results from the employees' need to belong to the organization (Fisher and Ashkanasy, 2000). Attitudinal pride can be viewed as a form of collective pride arising from the need for employees to be identified with a particular group, such as the organization for which they work (Babić-Hodović and Arslanagić-Kalajdžić, 2019; Lea and Webley, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attitudinal pride (in contrast to the individuality of emotional pride) is collective and results from the employees' need to belong to the organization (Fisher and Ashkanasy, 2000). Attitudinal pride can be viewed as a form of collective pride arising from the need for employees to be identified with a particular group, such as the organization for which they work (Babić-Hodović and Arslanagić-Kalajdžić, 2019; Lea and Webley, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the umbrella of consequences, the constructs identified under affective outcomes include trust, pride, job satisfaction, communal relationship (Babić-Hodović and Arslanagić-Kalajdžić, 2019; Esenyel, 2019; Esenyel and Emeagwali, 2019; Helm, 2011; Lee, 2020). These outcomes coincide with the end results of successful interpersonal relationships as determined by Hon and Grunig (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Two separate studies investigated the impact of internal reputation on employees' pride and job satisfaction (Babić-Hodović and Arslanagić-Kalajdžić, 2019; Helm, 2011). Helm’s (2011) study was based upon responses from employees of Fortune’s index of America’s Most Admired Companies, while Babíc-Hodović and Arslanagić-Kalajdžić’s (2019) was from frontline employees in professional services in a European country. Both studies showed positive associations.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased customer growth and a boost in sales [58]. As representatives of the corporate image, employees with direct customer contact are often seen as ambassadors, as they play an active role in the external communication [59] of SEOs. They are a valuable tool for monitoring immediate results in the context of service interactions and strategic initiatives [60].…”
Section: Hypothesis 2 (H2) a Positive Working Atmosphere Has A Positi...mentioning
confidence: 99%
“…They are a valuable tool for monitoring immediate results in the context of service interactions and strategic initiatives [60]. Customer satisfaction and loyalty are shaped by employees' understanding of their role within the service process [59,61].…”
Section: Hypothesis 2 (H2) a Positive Working Atmosphere Has A Positi...mentioning
confidence: 99%